Candida spp.: manual identification (reference method) and automated identification (Vitek system platform) - Mondelli, A. L. [UNESP]; Niero-Melo, L.; Bagagli, Eduardo [UNESP]; Camargo, C. H. [UNESP]; Bruder-Nascimento, A. [UNESP]; Sugizaki, M. F. [UNESP]; Carneiro, M.; Villas Boas, P. J. F. (Universidade Estadual Paulista (Unesp), Centro de Estudos de Venenos e Animais Peçonhentos (CEVAP), 2012)
Yeasts are becoming a common cause of nosocomial fungal infections that affect immunocompromised patients. Such infections can evolve into sepsis, whose mortality rate is high. This study aimed to evaluate the viability of Candida species identification by the automated system Vitek-Biomerieux (Durham, USA). Ninety-eight medical charts referencing the Candida spp. samples available for the study were retrospectively analyzed. The system Vitek-Biomerieux with Candida identification card is recommended for laboratory routine use and presents 80.6% agreement with the reference method. By separate analysis of species, 13.5% of C. parapsilosis samples differed from the reference method, while the Vitek system wrongly identified them as C. tropicalis, C. lusitaneae or as Candida albicans. C. glabrata presented a discrepancy of only one sample (25%), and was identified by Vitek as C. parapsilosis. C. guilliermondii also differed in only one sample (33.3%), being identified as Candida spp. All C. albicans, C. tropicalis and C. lusitaneae samples were identified correctly.
Keywords: candidemia; Candida spp.; identification; automated identification